Evaluation of work-related accidents in Sari forests exploitation workers - MB Khodaei; MK Eraghi; A Eghtesadi (طب کار)
Background: The exploitation of forests, which generally involve combinations of natural hazards, could damage the health and safety of forest workers. The aim of this study was to analyze the factors of the accidents that happened to Sari forests exploitation workers. Methods: This was a cross-sectional (descriptive-analytic) study. A number of 136 employees accident reports were recorded during the years 1388 to 1390 in the Sari country side forests have been studied. The relationship between events and causes of accidents, injuries and factors influencing the nature and unsafe circumstances, organs that injured and miss declaim were assessed. The data were analyzed with SPSS software. Results: Results showed that 53% of events due to the insecure conditions and 47 percent of events were due to unsafe conditions in the workplace. The organs that most injured were hand, foot and eye with 56, 51 and 18 cases respectively. Average of lost working hours were 11/66 hours of work per each incident. Conclusion: The main causes of these injuries were lack of personal protective equipment in unsafe acts and unsafe conditions are mechanical and physical factors, So the use of personal protective equipments, solve the mechanical problems, and train the workers against risks are useful methods. Mechanical and physical factors did not attempt to solve ratio problems